PENETAPAN STATUS TERSANGKA SEBAGAI OBJEK PRAPERADILAN - Salundik (Jurnal Ilmu Hukum Tambun Bungai, 2017)
The pretrial institution are for exercise horizontal oversight of the enforced action taken against the suspect as long as he is under investigation or prosecution, in order to ensure that such action is not inconsistent with the law and constitution.The pretrial object is limitative in that it is limited only to the validity of the arrest, detention, suspension of investigation, suspension of prosecution and on the request for compensation and rehabilitation by the suspect or his family or other parties for the proxy whose case is not brought to court.The entry of the determination of the suspect as a pretrial object is also stipulated by the Constitutional Court based on the Decision of the Constitutional Court Number 21 / PUU-XII / 2014. Expanding by adding some pretrial objects in article 77 letter a Criminal Procedure Code (KUHAP)namely the determination of suspects, Searches, and foreclosures. The consequences of the law after the pretrial verdict against the suspect are, certainly, based on the verdict of the judge presiding over the pretrial filed by the suspect or the applicant and can only be executed or held if it has a permanent legal force.If the pretrial is accepted then the suspect's status is denied and free by law whereas if the suspect's pretrial petition is rejected then the examination of the suspect is resumed in accordance with applicable law.